Scientific creativity: A bibliometric review and analysis - Surya Haryandi; Suyidno Suyidno; Misbah Misbah; Dewi Dewantara; Saiyidah Mahtari; Mohd Ali Ibrahim (Universitas PGRI Kanjuruhan Malang, 2021)
Scientific creativity is one of the higher-order thinking skills which are highly functional for each individual. Scientific creativity encourages the individual to not only generate creative ideas, but also promotes the notion of the appropriate technology. This article provides an in-depth explanation of the bibliometric analysis of scientific literature in education. The articles search was performed by utilizing Publish or Perish (PoP) software on the Crossref database. The search and sort results discovered that 28 of 200 articles were found between the years of 2019-2020. The selected metadata was edited using Mendeley Desktop software. The edited results were then analyzed further and visualized using the VOSviewer software. Overall, articles with the keyword scientific creativity published in the 2019-2020 period have not been cited, and it is essential to be studied collaboratively not only between national institutions but also internationally.